Aerodynamic Tailoring of Structures Using Computational Fluid Dynamics. Issue 1 (2nd January 2019) - Ding, Fei; Kareem, Ahsan; Wan, Jiawei
ABSTRACT: Tall buildings and long span bridges exposed to wind undergo complex interactions, which precludes a functional relationship between wind and its load effects. In digital age with burgeoning growth in computational resources and parallel advances in computational fluid dynamics, computational simulations are evolving with a promise of becoming versatile, convenient and reliable means of assessing wind load effects. This paper provides an overview of the current state-of-the-art on the CFD based simulations of wind loads on structures by delineating the differences in the modeling of streamline nature of airfoils versus complex profiles of civil structures. This is followed by highlighting the merits and shortcomings of three modeling schemes central to CFD, i.e. RANS, LES and DNS. Topics related to generation of inflow conditions and fluid-structure interactions are discussed. A case study involving aerodynamic shape sculpting of tall buildings that requires examining several configurations is presented. While such an assessment is currently performed via wind tunnels with limited set of configurations, CFD promises to discover the optimal configuration in a large search space. In closing, future prospects, e.g. advances in multi-fidelity models and the role and propagation of input and modeling uncertainties in CFD simulation are presented.